Health supports needed for homeless persons transitioning from hospitals. - Canham, Sarah L.; Davidson, Shelly; Custodio, Karen; Mauboules, Celine; Good, Chloe; Wister, Andrew V.; Bosma, Harvey (Health & Social Care in the Community, 2019)
Being homeless has a negative effect on health and the health needs of individuals experiencing homelessness are complex and challenging to address. As a result of limited access to and use of primary healthcare, the main point of entry into the healthcare system for individuals experiencing homelessness is often hospitals and emergency departments. Persons experiencing homelessness are commonly discharged from hospital settings to locations that do not support recovery or access to follow‐up care (e.g. shelters or the street). This can be costly to both the healthcare system and to individuals' health and quality of life. We conducted a scoping review of the literature published between 2007 and 2017 to identify the types of health supports needed for persons experiencing homelessness who are discharged from the hospital. Thirteen literature sources met inclusion criteria and thematic data analyses by two researchers resulted in the identification of six themes related to the types of health supports needed for persons experiencing homelessness who are transitioning (i.e. being discharged) from the hospital. Using a community consultation approach, the scoping review themes were validated with 23 health and shelter service providers and included in our integrated findings. Themes included: (a) a respectful and understanding approach to care, (b) housing assessments, (c) communication/coordination/navigation, (d) supports for after‐care, (e) complex medical care and medication management, and (f) basic needs and transportation. These themes were found to resonate with participants of the community consultation workshop. Recommendations for trauma‐informed care and patient‐ or client‐centred care approaches are discussed.